2021
DOI: 10.1080/21655979.2021.1985342
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-140-5p represses chondrocyte pyroptosis and relieves cartilage injury in osteoarthritis by inhibiting cathepsin B/Nod-like receptor protein 3

Abstract: represses chondrocyte pyroptosis and relieves cartilage injury in osteoarthritis by inhibiting cathepsin B/Nod-like receptor protein 3, Bioengineered,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Excessive pore formation compromises the integrity of the plasma membrane, causing a lytic form of cell death known as pyroptosis. A recent study has identified that CTSB as an autophagy regulator plays an active role in the degradation of autophagic substrate engaged in ferroptosis (a type of iron-dependent oxidative cell death driven by lipid peroxidation) ( 67 ). In addition to apoptosis and pyroptosis, other cell death patterns including necroptosis and alkaliptosis (a pH-dependent form of regulated cell death) have been shown to be caspase-dependent and to participate in the progression and development of pancreatic cancer ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive pore formation compromises the integrity of the plasma membrane, causing a lytic form of cell death known as pyroptosis. A recent study has identified that CTSB as an autophagy regulator plays an active role in the degradation of autophagic substrate engaged in ferroptosis (a type of iron-dependent oxidative cell death driven by lipid peroxidation) ( 67 ). In addition to apoptosis and pyroptosis, other cell death patterns including necroptosis and alkaliptosis (a pH-dependent form of regulated cell death) have been shown to be caspase-dependent and to participate in the progression and development of pancreatic cancer ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the membranes were incubated with primary antibodies at 4°C overnight. Blots were detected using an ECL kit (Thermo Fisher Scientific) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mounting evidence showed that exosomes, a type of extracellular vesicles released by astrocytes, act as a signaling transmitter among astrocytes, microglia, and neurocytes (9)(10)(11). By transporting protein or/and non-coding RNAs, exosomes play a pivotal role in triggering and regulating neuro-immune responses via adjacent and remote micro-communications.…”
Section: Introductionmentioning
confidence: 99%